Awareness and utilization of health insurance among patients of a tertiary care centre in South India - Luke, Swetha; Vincent, Jose (International Journal Of Community Medicine And Public Health, 2020)
Background: While health insurance may seem like just another form to fill, it has proven to be a literal life saver in case of medical catastrophes, saving those subscribed from possible health expense induced poverty. The objective of this study is to assess the proportion of patients aware of the provision of health insurance and have subscribed to them. Methods: Cross sectional study conducted in a tertiary care center based in South India during the period July 2019 to September 2019. Convenience sampling with a sample size of 58was used. Data collected with the help of an interviewer administered semi-structured questionnaire. Results: Awareness of the provision of health insurance was found to be as high as 89.7%. But only 51.7% were found to be subscribed to a health insurance plan. Of which 70% had joined a Government insurance scheme and 30% had a private health insurance. Conclusions: While a basic level of awareness is present, that itself does not lead to subscription to an insurance plan. The public should be exposed to the newer, more affordable government led plans which best suit their financial situations.